Xenon arc photocoagulation for the treatment of diabetic maculopathy. Interim report of a multicentre controlled clinical study. Issue 6 (June 1980) - Townsend, C; Bailey, J; Kohner, E
Abstract : The results of a randomised controlled clinical study in the treatment of diabetic maculopathy are reported. Ninety-nine patients with two similarly affected eyes had one--chosen by random procedure--treated, while the other was left as an untreated control. Visual acuity was maintained in the treated eyes, while it deteriorated in the untreated eyes, reaching over 2 lines difference after 4 years. The difference in deterioration was significantly less in treated than in untreated eyes at each assessment. After 4 years the difference between the 2 eyes was greatest in those with initially good vision. There was no difference in visual acuity in patients whose initial vision was less than 6/36. Only 9 treated but 25 control eyes lost vision to blindness (P less than 0.001). It is concluded that maculopathy is a treatable form of diabetic retinopathy if treated before severe visual loss occurs.